2005
DOI: 10.1115/1.2220050
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Some Improved Blade Tip Concepts

Abstract: Over tip leakage in high-pressure turbines contributes to aerodynamic losses and migration of hot gasses towards the tip resulting in increased thermal distress. Consequently, turbine designers continue to search for improved blade tip concepts that offer the promise of reducing tip leakage. The present paper deals with the computational fluid dynamics analyses of some such tip configurations. The geometries, patented by GE, are variants of a conventional squealer tip and include (i) a pressure side tip shelf … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(18 citation statements)
references
References 2 publications
0
18
0
Order By: Relevance
“…Although, the relation between leakage mass flow rate and losses/efficiency, i. e. as leakage mass flow rate increase, the losses/efficiency increases/decreases, holds true for the all cases except the modified tip. It was pointed out by Prakash et al 18) that it is not always true, as the losses depend on other factors besides the leakage mass flow rate (e. g., profile losses, secondary losses, etc.) which are affected by the different flow fields associated with different geometries.…”
Section: Leakage Mass Flow Rate and Total Pressure Lossmentioning
confidence: 99%
See 1 more Smart Citation
“…Although, the relation between leakage mass flow rate and losses/efficiency, i. e. as leakage mass flow rate increase, the losses/efficiency increases/decreases, holds true for the all cases except the modified tip. It was pointed out by Prakash et al 18) that it is not always true, as the losses depend on other factors besides the leakage mass flow rate (e. g., profile losses, secondary losses, etc.) which are affected by the different flow fields associated with different geometries.…”
Section: Leakage Mass Flow Rate and Total Pressure Lossmentioning
confidence: 99%
“…Their results showed that for the trip strips placed against the leakage flow, the heat transfer rate on the tip reduced by 10%-15% compared to the plain tip. Prakash et al 18) proposed two blade tip geometries; a pressure side tip shelf with vertical squealer tip wall, and a pressure side tip shelf with inclined squealer tip wall. They found that the inclined wall case reduced the leakage mass flow and improved efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…The term "weakening the tip vortex" was equivalent to a reduction in the momentum deficit contained in the tip vortex area. Prakash et al [8] provided a numerical investigation of a conventional squealer tip with a straight shelf and inclined shelf near the pressure side in an effort to control the leakage flow. The computations showed that the specific shelf designs applied to the pressure side of the tip region were highly effective in weakening the tip vortex.…”
Section: Reducing the Discharge Coefficient C Dmentioning
confidence: 99%
“…Krishnababu et al 10) compared the performance of the double squealer to that of suction side squealer, and they showed that the double squealer reduced the leakage mass flow rate whereas the suction side squealer increased it. Prakash et al 11) proposed two blade tip shapes: a pressure side tip shelf with a vertical squealer tip wall and a pressure side tip shelf with an inclined squealer tip wall, which reduces the leakage mass flow and improves efficiency. Mischo et al 12) also proposed an improved design of the double squealer tip for a highly loaded axial turbine rotor blade.…”
Section: Introductionmentioning
confidence: 99%